Tecnologia social para autogestão : um estudo em empreendedorismo econômico solidário da cadeia produtiva da cajucultura no Rio Grande do Norte - Albuquerque, Francivaldo dos Santos (2013)
The theme of this dissertation is social technology for self-management: a study in economic enterprise supportive of Rio Grande do Norte. The research aimed to obtain evidence that the reapplication of technology management, basic economic-financial and pricing, as production costs, has the potential to contribute to the self-management of APABV. The social technology and self-management are theoretical frameworks used and where workers are central figures in both the generation and replication of technologies that are compatible with their realities, as in the conduct and management approach adopted by them in their venture, they are makers decisions. To achieve the proposed objective was accomplished participatory research, which was used in addition to document analysis, participatory methodologies such as the construction of the DRP, group interview, experience in the production environment and family of entrepreneurs APABV. This research allowed the management technologies such as spreadsheets controls basic economic and financial costs, when socialized and understood by workers has the potential informational and become part of their daily decision-making process of the project, making up social technology